Respuesta :
Answer:
4.55
Step-by-step explanation:
Average Rate of Change formula :
[tex]A(x) = \frac{f(b)-f(a)}{b-a}[/tex]
============================================================
Solving :
⇒ A(x) = [tex]\frac{f(6)-f(3)}{6-3}[/tex]
⇒ A(x) = 22.466436 - 8.81340423 / 3
⇒ A(x) = 13.6530318/3
⇒ A(x) = 4.55 (rounded to 2 decimal places)
Find the average rate of change of the exponential equation from x = 3 to x = 6
f(x) = 2x^1.35
- Average = 22.466436 - 8.81340423 / 3
- Average = 13.6530318/3
- Average = 4.55 (rounded to 2 decimal)
i hope it helps